Can Fiber-reinforced Composites Increase the Fracture Resistance of Direct Composite Restorations in Structurally Compromised Teeth? A Systematic Review and Meta-analysis of Laboratory Studies - Bijelic-Donova, J; Bath, A K; Rocca, G T; Bella, E di; Saratti, C M (Operative dentistry, 2025)
OBJECTIVE: Systematic review and meta-analysis on laboratory studies aimed to answer whether there is a difference in fracture resistance and fracture mode of structurally compromised teeth restored with direct composite restorations reinforced with short glass-fiber or bidirectional polyethylene fiber substructure, and between the two different fiber-reinforcement types. METHODS: An electronic literature search was conducted in Medline, Scopus, Web of Science, Lilacs, Google Scholar, Cochrane Library, and University Library databases. The last search was conducted on 16 November 2023. Only studies looking at Ribbond-reinforced restorations and/ or the use of EverX Posterior within restorations were included. Data were categorized and analyzed based on specific outcome measures including fracture resistance and fracture mode. Data from individual studies were divided into premolars and molars for each material category and then collated to compare the mean differences in fracture resistance between control groups (composite restorations) and intervention groups (fiber-reinforced composite restorations). RESULTS: From the initial 1266 articles identified, 23 laboratory-based studies were included for quantitative analysis. Twenty articles had an overall low risk of bias and 3 had an overall unclear risk of bias. The pooled estimate of the effect favored the intervention groups as having statistically significant higher fracture resistance when compared to control groups. CONCLUSIONS: Both fiber types improve fracture resistance and the fracture mode of structurally compromised teeth is equally efficient. Application technique deserves attention. Ribbond could be placed in a single layer at the cavity floor, whereas EverX Posterior should replace missing dentin in an anatomically shaped way.
Keywords: sklo; složené pryskyřice; Glass; Polyethylenes; lidé; trvalá zubní náhrada; Dental Restoration Failure; Dental Restoration, Permanent; zubní materiály; zuby-sanace - selhání; fraktury zubů; polyethyleny; Dental Materials; Composite Resins; Tooth Fractures; Humans